2004
DOI: 10.1017/s0950268804002705
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antibiotic resistance of clinical and environmental Vibrio cholerae suggests that many serogroups are reservoirs of resistance

Abstract: Vibrio cholerae is an important human pathogen and the cause of cholera. Since genetic variation and antibiotic resistance of strains have implications for effective treatment of the disease, we examined the genetic diversity and antibiotic resistance profile in 92 clinical strains (serogroup O1) and 56 environmental strains (O1 antigen, 42 strains; non-O1 antigen, 14 strains) isolated in Brazil between 1991 and 1999. Clinical and environmental O1 strains showed greater drug resistance compared to environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…However, the qacEΔ1 and sulI genes, which define the 3'CS, were present. This result contrasts with a previous work that was unable to show class 1 integrons in V. cholerae O1 strains from the Brazilian cholera epidemic (Campos et al 2004).…”
contrasting
confidence: 99%
“…However, the qacEΔ1 and sulI genes, which define the 3'CS, were present. This result contrasts with a previous work that was unable to show class 1 integrons in V. cholerae O1 strains from the Brazilian cholera epidemic (Campos et al 2004).…”
contrasting
confidence: 99%
“…isolated from the Chesapeake Bay (36), the non-O1/non-O139 V. cholerae isolates in this study showed lower levels of resistance to ampicillin and penicillin (9 to 20%) than those of V. parahaemolyticus (53 to 68%) and showed intermediate resistance to streptomycin compared to V. vulnificus (36). Penicillin resistance, almost ubiquitous in both clinical and environmental V. cholerae isolates worldwide (23,25), is likely associated with mutations of penicillin binding proteins 1 and/or 2, as observed for several sequenced V. cholerae strains (i.e., N16961, MJ-1236, and MO10). Ampicillin resistance has been reported for clinical non-O1/non-O139 V. cholerae and V. parahaemolyticus strains isolated in Maryland as early as 1984 (37).…”
Section: Discussionmentioning
confidence: 58%
“…The intensive use of antibiotics in medicine and in animal farming has been suggested to be the source of such resistance (34,35), and V. cholerae strains isolated from seawater have been shown to be antibiotic resistant (23,24). The data presented here provide the first report of antimicrobial susceptibility for non-O1/non-O139 V. cholerae from the Chesapeake Bay.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The more frequently used techniques involve multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), restriction fragment length polymorphism (RFLP) studies [ 16 20 ]. An old method of differentiation concerns phenotyping as enzyme profiles of bacterial strains [ 37 40 ]. Multilocus enzyme electrophoresis (MLEE) could be compared to the analysis of antibiotic zones of inhibition.…”
Section: Resultsmentioning
confidence: 99%